PEMBINAAN PAK BAGI REMAJA SMP NEGERI 1 SEMAU SELATAN DI ERA DIGITALISASI - Tri Oktavia Oematan; Maria Indriani Sesfao; Januar Daniel Rohi; Catur Prio Purnomo; Yuniarti Ablelo (Jurnal Abdi Insani, 2023)
Technology actually provides many conveniences for people in carrying out various activities. In recent decades, many facilities have been enjoyed thanks to the sophistication they have developed. However, apart from that, technological advances also have a negative influence on people's lives, especially teenagers. Through digitalization, addiction, abuse, and the influence of content can damage teenage behavior. The purpose of this service activity is to provide education and encouragement for the youth of SMP Negeri 1 Semau Selatan so that they can wisely use the technology that is increasingly developing so that it does not damage their character. The method for carrying out PKM, "Development of PAK for Christian Youth in the Digitalization Era at SMP N 1 Semau Selatan," is divided into the following stages: 1) This community service activity begins with conducting an initial (online) survey together with the principal of SMP Negeri 1 Semau Selatan. The values of Christian Religious Education (PAK) are important to convey to teenagers so that teenagers at Semau Selatan 1 Public Middle School can act wisely in the digitalization era, remain faithful in faith in the Lord Jesus, and not be affected by the negative things offered by technological advances.